AUDIT APLIKASI ONLINE DATA SISTEM (ODS) MENGGUNAKAN COBIT 4.1 - Uyunun Lusiana; Khairul Imtihan; Mohammad Taufan Asri Zaen (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
Online Data System (ODS) is a web-based system used to manage and monitor data on Cooperatives and Small and Medium Enterprises (SMEs) in Central Lombok Regency. The audit uses the COBIT 4.1 framework. The ODS audit process includes defining business goals based on the vision and mission of the Department of Cooperatives and SMEs of Central Lombok Regency, determining IT goals based on these business goals, identifying IT processes, and calculating the maturity level as a basis for providing recommendations. Based on the vision, mission, and issues identified from interviews with the Head of the Department of Cooperatives and SMEs, the selected domains are PO7 (Manage IT Human Resources), AI2 (Acquire and Maintain Application Software), and DS5 (Ensure Systems Security). The maturity level calculations resulted in the following scores: PO7 scored 2.54, AI2 scored 2.80, and DS5 scored 2.52. Based on these maturity level scores, the processes are at the Defined Process maturity stage. Overall, the processes or activities in the Department of Cooperatives and SMEs are at the Defined Process maturity level